Tremelimumab as second-line or third-line treatment in relapsed malignant mesothelioma (DETERMINE): a multicentre, international, randomised, double-blind, placebo-controlled phase 2b trial. Issue 9 (September 2017) - Maio, Michele; Scherpereel, Arnaud; Calabrò, Luana; Aerts, Joachim; Perez, Susana Cedres; Bearz, Alessandra; Nackaerts, Kristiaan; Fennell, Dean A; Kowalski, Dariusz; Tsao, Anne S; Taylor, Paul; Grosso, Federica; et al.
Summary: Background: New therapeutic strategies for malignant mesothelioma are urgently needed. In the DETERMINE study, we investigated the effects of the cytotoxic-T-lymphocyte-associated antigen 4 (CTLA-4) monoclonal antibody tremelimumab in patients with previously treated advanced malignant mesothelioma. Methods: DETERMINE was a double-blind, placebo-controlled, phase 2b trial done at 105 study centres across 19 countries in patients with unresectable pleural or peritoneal malignant mesothelioma who had progressed after one or two previous systemic treatments for advanced disease. Eligible patients were aged 18 years or older with Eastern Cooperative Oncology Group performance status of 0 or 1 and measurable disease as defined in the modified Response Evaluation Criteria In Solid Tumors (RECIST) version 1.0 for pleural mesothelioma or RECIST version 1.1 for peritoneal mesothelioma. Patients were randomly assigned (2:1) in blocks of three, stratified by European Organisation for Research and Treatment of Cancer status (low risk vs high risk), line of therapy (second line vs third line), and anatomic site (pleural vs peritoneal), by use of an interactive voice or web system, to receive intravenous tremelimumab (10 mg/kg) or placebo every 4 weeks for 7 doses and every 12 weeks thereafter until a treatment discontinuation criterion was met. The primary endpoint was overall survival in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of study drug. The trial is ongoing but no longer recruiting participants, and is registered with ClinicalTrials.gov, number NCT01843374 . Findings: Between May 17, 2013, and Dec 4, 2014, 571 patients were randomly assigned to receive tremelimumab (n=382) or placebo (n=189), of whom 569 patients received treatment (two patients in the tremelimumab group were excluded from the safety population because they did not receive treatment). At the data cutoff date (Jan 24, 2016), 307 (80%) of 382 patients had died in the tremelimumab group and 154 (81%) of 189 patients had died in the placebo group. Median overall survival in the intention-to-treat population did not differ between the treatment groups: 7·7 months (95% CI 6·8–8·9) in the tremelimumab group and 7·3 months (5·9–8·7) in the placebo group (hazard ratio 0·92 [95% CI 0·76–1·12], p=0·41). Treatment-emergent adverse events of grade 3 or worse occurred in 246 (65%) of 380 patients in the tremelimumab group and 91 (48%) of 189 patients in the placebo group; the most common were dyspnoea (34 [9%] patients in the tremelimumab group vs 27 [14%] patients in the placebo group), diarrhoea (58 [15%] vs one [<1%]), and colitis (26 [7%] vs none). The most common serious adverse events were diarrhoea (69 [18%] patients in the tremelimumab group vs one [<1%] patient in the placebo group), dyspnoea (29 [8%] vs 24 [13%]), and colitis (24 [6%] vs none). Treatment-emergent events leading to death occurred in 36 (9%) of 380 patients in the tremelimumab group and 12 (6%) of 189 in the placebo group; those leading to the death of more than one patient were mesothelioma (three [1%] patients in the tremelimumab group vs two [1%] in the placebo group), dyspnoea (three [1%] vs two [1%]); respiratory failure (one [<1%] vs three [2%]), myocardial infarction (three [1%] vs none), lung infection (three [1%] patients vs none), cardiac failure (one [<1%] vs one [<1%]), and colitis (two [<1%] vs none). Treatment-related adverse events leading to death occurred in five (1%) patients in the tremelimumab group and none in the placebo group. The causes of death were lung infection in one patient, intestinal perforation and small intestinal obstruction in one patient; colitis in two patients, and neuritis and skin ulcer in one patient. Interpretation: Tremelimumab did not significantly prolong overall survival compared with placebo in patients with previously treated malignant mesothelioma. The safety profile of tremelimumab was consistent with the known safety profile of CTLA-4 inhibitors. Investigations into whether immunotherapy combination regimens can provide greater efficacy than monotherapies in malignant mesothelioma are ongoing. Funding: AstraZeneca.